IMPROVING THE OCCUPATIONAL HEALTH AND SAFETY TRAINING SYSTEM IN LUKOIL-WESTERN SIBERIA LLC - Yulia F. Yakovleva; Inna V. Ozden (Oil and Gas Business, 2026)
This article proposes improvements to the occupational safety training system at LUKOIL-Western Siberia LLC for methanol handling. The relevance of the study is due to the high toxicity and fire hazard of methanol, as well as the ineffectiveness of traditional forms of personnel training. An analysis of the current employee training and knowledge monitoring system was conducted, identifying key shortcomings: the formal nature of training, insufficient practical focus, and limited use of modern training methods. Based on a staff survey, problem areas were identified and areas for improvement were proposed. Measures to improve the effectiveness of personnel training are proposed, including strengthening the practical component of training and introducing modern educational technologies. Implementation of these measures will contribute to increased employee knowledge and a reduction in occupational risks associated with methanol handling.